Research trends and network approach of critical thinking skills in English Language Teaching – A bibliometric analysis implementing R studio - M.P. Arthi; S.N.S. Gandhimathi (Heliyon)
Critical thinking is often regarded as one of the vital skills in the 21st century. In recent years, it has become important to combine this skill with other skills such as language learning, creativity, problem-solving, decision making, and reflective thinking. As language and thoughts are intertwined and influence each other, incorporating thinking skills into English Language Teaching (ELT) can enhance academic and professional success. The prime objective of the current study is to conduct a bibliometric analysis of research on Critical Thinking (CT) in ELT from 2012 to 2022 by focusing on publication and research trends such as influential authors, globally cited documents, pertinent journals, leading countries, and significant affiliations. The current study also sheds light on the co-occurrence of keywords and thematic evolution through bibliometric analysis, examining 238 articles from Scopus and Web of Science databases using R studio (Biblioshiny). This bibliometric analysis highlights Thinking Skills and Creativity as the most pertinent journal with high citation count and China being the most cited country in this field. It also accentuates the interconnection between higher-order thinking skills, self-regulation, critical thinking, and critical reading. The thematic evolution of CT shows a shift from collaborative learning and CT (2012–2019) to language teaching and CT (2020–2022). It emphasizes the importance and the rising prominence of CT skills in language teaching. Moreover, this review will guide scholars and academicians to identify future research directions in the field of CT.